Direction Analysis of Student Research Topics During Covid-19 Pandemic - Syaharuddin Syaharuddin; Emilia Silvana Sitompul; Deni Apriansyah; Awaluddin Hasrin; Sri Mulyono; Sumarni Sumarni (IJECA (International Journal of Education and Curriculum Application), 2020)
The Covid-19 pandemic has reduced field activity, especially for students who will research their final task. This article aims to explain (1) the direction of research topics selected and conducted by students and (2) learning media plans implemented during covid-19. We have spread the questionnaire online to several colleges so that 146 respondents are acquired. The results of the questionnaire were analyzed using descriptive statistics as well as qualitative analysis to look at concepts or variables as well as reference sources used by students in determining the topic of research. The results showed that the research topics chosen by students did not all lead to the development of ICT-based learning media during the Covid-19 period. This is seen from 61.64% choosing qualitative variable studies to facilitate the process of retrieving data through the spread of online polls. From this result, it is also seen that the influence of the Covid-19 pandemic on the determination of student research topics is only 17.12%.